Research on Children’s Cognitive Education Based on Pathological Linguistics - Yuefang Hou (Occupational Therapy International)
The value of pathological linguistics in children’s cognitive development has attracted more and more experts’ attention. Based on pathological linguistics, this paper establishes an intervention system for children’s cognition-language assessment and cognitive education, guided by a set of fixed procedures, which can quickly collect children’s speech data in a short period of time. Based on this evaluation paradigm, the lab collected a large number of speech data of children aged 2-14 in the process of verbal communication. Based on the six linguistic dimensions of phonology, productivity, fluency, grammar, semantics, and logic, the corpus was subdivided into 16 indicators for manual annotation and machine recognition. A cognitive-language assessment database is established for language ability assessment and language barrier screening, and on this basis, the children’s language assessment and cognitive education intervention system is completed based on six modules: user, assessment, scale, resources, teaching, and data. Through experimental research, this paper proves that there are differences in the contribution rates of six language dimensions to the screening of children’s language disorders, and the top three are fluency (29.6%), pronunciation (25.7%), and productivity (19.3%). By analyzing the contribution rates, the development of children’s comprehensive speech ability can be evaluated more accurately. The early intervention education of children’s cognition has a great relationship with their comprehensive language ability. The intervention education before the age of 3 is beneficial to the language development of children with disabilities. Children’s cognitive education has improved in cognitive performance, cognitive generalization level, emotional cognition, and language expression, indicating that the use of cognitive education system has a good effect, improving the level of children’s cognitive education.